Pengaruh Struktur Aktiva, Ukuran Perusahaan, Operating Leverage dan Pertumbuhan Penjualan Terhadap Struktur Modal Pada Perusahaan Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (2017-2020): Bahasa Indonesia - Deasy Arisandy Aruan; Putri Sitanggang; Catrin Naomi Lumban Tobing; Lasriana Harianja (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the effect of asset structure, firm size, operating leverage and sales growth on capital structure of food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020. The data used is sourced from financial data on the Indonesia Stock Exchange through the website www.idx.co.id , and a selection has been made according to predetermined criteria. The population used in this study is Food and Beverage companies, totaling 30 companies, by using a purposive sample, the resulting sample is 17 companies. With this research, it is hoped that it can become a science to help further researchers as well as students or the general public who need a source of information. From the research, it can be seen that Asset Structure, Company Size, Operating Laverage and Sales Growth have a positive and significant effect simultaneously on profit growth. Asset structure and firm size have a negative and insignificant effect on profit growth. Operating leverage has a positive and significant effect on profit growth while Sales Growth has a positive but not significant effect on profit growth in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2020 period.